Community-Based Research among Marginalized HIV Populations: Issues of Support, Resources, and Empowerment - Mario Brondani; Nardin R. Moniri; R. Paul Kerston (Interdisciplinary Perspectives on Infectious Diseases)
A research question was posed to us by a local HIV-resource organization interested in exploring the educational and service needs of those unreached. In order to properly address this inquiry, we developed a community-based participatory research by training peer-led volunteers to facilitate focus-group discussions within Aboriginal and refugees participants following an interview guide. We gathered Aboriginal people and refugees separated into three focus groups each, enrolling a total of 41 self-identified HIV-positive, 38 males. The discussions were tape recorded upon consent and lasted between 59 and 118 minutes. We analyzed the thematic information collected interactively through constant comparison. The qualitative data leading to categories, codes, and themes formed the basis for the spatial representation of a conceptual mapping. Both groups shared similar struggles in living with HIV and in properly accessing local nonmedical HIV resources and discussed their concerns towards the need for empowerment and support to take control of their health.